Implementation of Public Policy - Towalu, Harson (Publikasi Indonesia, 2022)
Population development policies related to national and regional development need to be strengthened both conceptually and practically. At the policy level, population development must be able to integrate national and regional population issues to create the concept of population-oriented development. The purpose of this study is to describe population development policies in Boalemo Regency related to policy implementation; policy concept; and the situation and conditions of population development. The method used is Observation; Documentation; and FGD, with the support of secondary data analysis and document review. The results of the study indicate that generally the implementation of population development policies in the Boalemo district has been carried out optimally, but still needs to be improved, especially in: Population Quantity Development Policy; Population Quality; Family planning; Mobility; and Population data and information. The implementation of Population-oriented Development Policies and Sustainable Population Development need to be given top priority. For this reason, a very important factor to improve is the Human Development Index (IPM)